UNDERSTANDING AND DIFFICULTIES OF MATHEMATICAL CONTENT TEACHED IN BASIC EDUCATION IN A STATE PUBLIC SCHOOL IN THE MUNICIPALITY OF PIUM-TO (REMUNOM, 2024)
Students have difficulty understanding the mathematical content taught by teachers. A lack of teaching infrastructure, trauma from previous grades and psychological factors are some of the reasons for these difficulties. Given the preceding, the investigation was initiated to comprehend the difficulties encountered in comprehending the mathematical concepts taught to first-year high school students in a public state school situated in the municipality of Pium–TO. June 2023 saw the research carried out in a quantitative manner, quantifying and transforming the research findings into numbers and percentages. The location investigated was a high school in the city of Pium, state of Tocantins, with 300 students enrolled, having access to textbooks and the internet, and having permanent instructors. Data was collected using a semi-structured questionnaire consisting of open and closed questions. 50 students in the first year of high school were interviewed for the questionnaire. 40% of people enjoy studying mathematics, with 52% dedicating less than 1 hour to studying and 70% considering it to be difficult to understand. The study revealed that 76 percent of learners cited the teacher's use of explanation as a teaching technique, and 80% claimed that the teacher doesn't employ any materials during classes. 56% of people don't know what mathematics is or what it's for, 72% don't understand and relate mathematical concepts, 80% have difficulty interpreting questions, and 88% don't have calculation skills. It is necessary to develop teaching strategies that help students understand when teaching mathematical content in the classroom, motivating and awakening students interest in the subject of Mathematics so that it becomes less abstract.